The Characteristic Features of Social Dialogue in the Baltics - Dvorak, Jaroslav; Karnite, Raita; Guogis, Arvydas (Socialinė teorija, empirija, politika ir praktika, 2018)
This article analyzes the characteristic features of social dialogue in the Baltic states. The methodology of the current research is based on an intensive analysis of literature and statistical data. The aim of the present research is to address some gaps that were identified during the literature review. Firstly, why does the social dialogue develop so slowly in the Baltic states? Secondly, what was the role of social partners in that process? We find that the main achievement in social dialogue have been reached by social partners on the national level and, despite the painful austerity measures, the Baltic states showed the benchmark of advanced crisis management.